Lactate provides a strong pH-independent ventilatory signal in the facultative air-breathing teleost Pangasianodon hypophthalmus - Mikkel T. Thomsen (Nature Portfolio, 2017)
Abstract Fish regulate ventilation primarily by sensing O2-levels in the water and arterial blood. It is well established that this sensory process involves several steps, but the underlying mechanisms remain frustratingly elusive. Here we examine the effect of increasing lactate ions at constant pH on ventilation in a teleost; specifically the facultative air-breathing catfish Pangasianodon hypophthalmus. At lactate levels within the physiological range obtained by Na-Lactate injections (3.5 ± 0.8 to 10.9 ± 0.7 mmol L−1), gill ventilation increased in a dose-dependent manner to levels comparable to those elicited by NaCN injections (2.0 µmol kg−1), which induces a hypoxic response and higher than those observed in any level of ambient hypoxia (lowest PO2 = 20 mmHg). High lactate concentrations also stimulated air-breathing. Denervation of the first gill arch reduced the ventilatory response to lactate suggesting that part of the sensory mechanism for lactate is located at the first gill arch. However, since a residual response remained after this denervation, the other gill arches or extrabranchial locations must also be important for lactate sensing. We propose that lactate plays a role as a signalling molecule in the hypoxic ventilatory response in fish.